Real Time FRET Based Detection of Mechanical Stress in Cytoskeletal and Extracellular Matrix Proteins - Meng, Fanjie (2011)
A molecular force sensing cassette (stFRET) was incorporated into actinin, filamin, and spectrin in vascular endothelial cells (BAECs) and into collagen-19 in Caenorhabditis elegans. To estimate the stress sensitivity of stFRET in solution, we used DNA springs. A 60-mer loop of single stranded DNA was covalently linked to the external cysteines of the donor and acceptor. When the complementary DNA was added it formed double stranded DNA with higher persistence length, stretching the linker and substantially reducing FRET efficiency. The probe stFRET detected constitutive stress in all cytoskeletal proteins tested, and in migrating cells the stress was greater at the leading edge than the trailing edge. The stress in actinin, filamin and spectrin could be reduced by releasing focal attachments from the substrate with trypsin. Inhibitors of actin polymerization produced a modest increase in stress on the three proteins suggesting they are mechanically in parallel. Local shear stress applied to the cell with a perfusion pipette showed gradients of stress leading from the site of perfusion. Transgenic C. elegans labeled in collagen-19 produced a behaviorally and anatomically normal animal with constitutive stress in the cuticle. Stretching the worm visibly stretched the probe in collagen showing that we can trace the distribution of mean tissue stress in specific molecules. stFRET is a general purpose dynamic sensor of mechanical stress that can be expressed intracellularly and extracellularly in isolated proteins, cells, tissues, organs and animals.